Graphene Oxide Nanoparticle–Loaded Ginsenoside Rg3 Improves Photodynamic Therapy in Inhibiting Malignant Progression and Stemness of Osteosarcoma - Lu, Shou-Liang; Wang, Yan-Hua; Liu, Guang-Fei; Wang, Lu; Li, Yong; Guo, Zhi-Yuan; Cheng, Cai (Frontiers in Molecular Biosciences, 2021)
Osteosarcoma serves as a prevalent bone cancer with a high metastasis and common drug resistance, resulting in poor prognosis and high mortality. Photodynamic therapy (PDT) is a patient-specific and non-invasive tumor therapy. Nanoparticles, like graphene oxide, has been widely used in drug delivery and PDT. Ginsenoside Rg3 is a principle ginseng component and has presented significant anti-cancer activities. Here, we constructed the nanoparticles using GO linked with photosensitizer indocyanine green (ICG), folic acid, and polyethylene glycol (PEG), and loaded with Rg3 (PEG-GO-FA/ICG-Rg3). We aimed to explore the effect of PEG-GO-FA/ICG-Rg3 combined with PDT for the treatment of osteosarcoma. Significantly, we found that Rg3 repressed proliferation, invasion and migration, and enhanced apoptosis and autophagy of osteosarcoma cells, while the PEG-GO-FA/ICG-Rg3 presented a higher activity, in which NIR laser co-treatment could remarkably increase the effect of PEG-GO-FA/ICG-Rg3. Meanwhile, stemness of osteosarcoma cells-derived cancer stem cells was inhibited by Rg3 and PEG-GO-FA/ICG-Rg3, and the combination of PEG-GO-FA/ICG-Rg3 with NIR laser further significantly attenuated this phenotype in the system. Moreover, NIR laser notably improved the inhibitor effect of PEG-GO-FA/ICG-Rg3 on the tumor growth of osteosarcoma cells in vivo. Consequently, we concluded that PEG-GO-FA/ICG-Rg3 improved photodynamic therapy in inhibiting malignant progression and stemless of osteosarcoma cell. Our finding provides a promising and practical therapeutic strategy for the combined treatment of osteosarcoma.